The Effect of Education with an Islamic Approach Addition in the Diffusion of Innovation for Oral Health Maintenance Using Siwak - Lastati Lastati; Taufan Bramantoro; Anis Irmawati (JURNAL INFO KESEHATAN, 2025)
The WHO states that tooth decay is the most common chronic disease experienced by people around the world. The result of the 2023 SKI shows that, on average, people aged ≥ 3 years in the last year complained of having dental and oral problems. One of the teachings of Islam regarding health is the Islamic recommendation on dental and oral health, and one of the things recommended by the Prophet Muhammad is to use a miswak. Islamic boarding schools are expected to educate their student in all aspects in accordance with Islamic values and norms, including aspects of dental and oral health. This study aims to analyze the differences in education with the addition of an Islamic approach in the diffusion of innovation in oral health maintenance using siwak. This approach is examined through five characteristics of innovation according to the theory of innovation diffusion, namely relative advantage, compatibility, complexity, triability, and observability. The research method used a quasi-experimental design with two treatment groups: education without the addition of an Islamic approach and education with the addition of an Islamic approach. The sampling technique used was purposive sampling, and the total number of respondents in this study was 60 students. The result shows that education with the addition of an Islamic approach showed a significant increase in the characteristics of triability and observability, and generally yielded higher scores compared to education without the addition of an Islamic approach. The Islamic approach was proven to be more effective in increasing respondents' decisions to use siwak and had a strong influence on the persuasion stage in the innovation adoption process. The conclusion is that the integration of religious values into health education can strengthen public acceptance and intention toward innovations in dental care based on the Sunnah.